Textbook of cardiovascular medicine - Topol, Eric J. 1954-; Califf, Robert M. (Lippincott Williams & Wilkins, 2007)
Updated throughout by renowned international authorities, Dr. Topol's best-selling text provides a comprehensive, contemporary view of every area of cardiovascular medicine, preventive cardiology; clinical cardiology; cardiovascular imaging; electrophysiology and pacing; invasive cardiology and surgical techniques; heart failure and transplantation; molecular cardiology; and vascular biology and medicine. DVD contains the full text, plus heart sounds, an image/chart/table bank, and videos of procedures, catheterization, CT/MRI, echocardiography, electrophysiology and pacing, intravascular ultrasonography, nuclear cardiology, and surgery.